The Role of Artificial Intelligence (AI) Technology in the Development of Early English Teaching Materials - Novitasari, Yesi; Bastian, Adolf; Reswita, Reswita; Wahyuni, Sri (Civiliza Publishing, Indonesia., 2025)
English has long been recognized as the dominant international language in various aspects of global life, from international communication and higher education to mastery of technology and science. The purpose of this study is to explore the role of AI in developing early English language teaching materials and identify its opportunities and challenges in early childhood education. This research method uses a quantitative approach. The sample of this study included 10 teachers at TKIT Model Madani Arrahman Pekanbaru City. The results show that teachers at TKIT Model Madani Arrahman Pekanbaru have sufficient initial knowledge of AI technology, although it is still limited to general use and has not been fully directed at developing teaching materials. AI is considered to play a role in helping teachers create more varied, interesting, and enjoyable English teaching materials for early childhood. However, the implementation of AI still faces technical obstacles, limited resources, and the need to adapt content to the characteristics of early childhood. Thus, AI has great potential in supporting the development of early childhood English teaching materials, but it needs to be supported by training, infrastructure, and strengthening teacher capacity for optimal and contextual implementation.